Role of Endophytes in Crop Production - Mistry, Sneha; Dand, Jalpa J.; Shinde, Manisha (Microbiology and Biotechnology Research: An Overview Vol. 3, 2025)
Endophytes, typically fungal or bacterial microbes residing within plant tissues without causing disease, hold promise for revolutionising crop production. The plant–endophyte relationship is a mutualistic symbiosis, characterised by endophytes residing within plant tissues without causing harm. Endophytes enhance host plant survival against biotic and abiotic challenges by directly improving nutrient uptake and modulating plant hormones. Indirectly, they contribute to plant health by deterring pathogens with antibiotics and enzymes, reducing nutrient availability for pathogens and activating defence mechanisms. This review delves into their diverse mechanisms, offering sustainable alternatives to chemical interventions. Understanding their role in stress alleviation is crucial for advancing agricultural practices and ensuring global food security. Crop production is the foundation of global food security, and ensuring that there is enough food to feed the ever-growing global population is necessary. Currently, it has been estimated that approximately. 20% of the total cultivable land faces saline stress globally, and this will reach 30% by 2050.